The Effect of Company Profitability and Size on Corporate Social Responsibility Disclosure (Study on Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange 2016-2020 Period) - Bambang Subiyanto; Arni Karina; Dewandaru Agung Pramita; Nadya Putri Alvionita (Budapest International Research and Critics University, 2022)
This study aims to determine whether Profitability and Company Size affect corporate social responsibility disclosure in Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange (IDX). 2016-2020 period. The sample in this study amounted to 25 companies obtained based on the purposive sampling method. The data in this study were obtained through documentation and taking secondary data. This study uses multiple linear regression analysis techniques assisted by using the SPSS Version 25 application. This study indicates that profitability has a positive and significant effect on the disclosure of Corporate Social Responsibility, and company size has no effect on the disclosure of Corporate Social Responsibility.